Effects of afforestation methods on nutrient runoff and fertility quality of red soil - ZHANG Ming-kui; XU Jian-ming (浙江大学学报. 农业与生命科学版, 2000)
Based on the measured data of soil nutrients and soil erosion, three afforestation methods, including controlled burning, full cultivation and bunch plantation, were compared. The results showed that both controlled burning and full cultivation enhanced erosion of soil and nutrients, caused decrease of organic matter, nitrogen, phosphate and potassium and led to degradation of soil fertility quality.